THE EVALUATION OF THE CORTISOL TITERS DYNAMIC IN THE BLOOD OF RATS CORONARY SINUS UNDER THE SIMULATED PITUITRIN-IZADRYNE MYOCARDIAL INFARCTION - Петрик, І.О.; Ходаківський, О.А.; Прокопенко, С.В. (World of Medicine and Biology, 2016)
The acute (7 days) and recovery (21 days) periods of pituitrin-izadryne infarction (MI) in rats are followed by the increase of cortisone titers in the blood of the coronary sinus by 6.13 and 3.58 times respectively, which points both at the distress progression in conditions of the acute coronary syndrome and the steroid cardiotoxicity development. The preventive-therapeutic intraperitoneal administration of Corvitin (10 mg/kg intraperitoneal) to rats prevents the development of the above-mentioned pathology attested by the probable de-escalation of cortisol titers in the acute and recovery periods of myocardial infarction compared to the control pathology group at an average by 5.79 and 3.82 times, respectively. The prophylactic administration before ischemia simulating and subsequent therapeutic administration during acute and recovery periods of MI 3,2’-spiro-pyrrolo-2-oxyndole derivate (compound R-86) at a conditionally effective dose of 10 mg/kg intragastrically completely prevented the escalation of the investigational hormone level confirmed by the absence of reliable differences in the cortisol level of intact group of animals. The modulating effect of 3,2’-spiro-pyrrolo-2-oxindole derivative (compound R-86) and Corvitin on the steroid cardiotoxicity developing may be one of mechanisms of its cardioprotective action.